Expanding the Victorian Alcohol Interlock Program to All Convicted Drink-Drivers - Chris Freethy (Journal of Road Safety, 2015)
The Victorian Alcohol Interlock Program was established in 2003 and expanded in 2006. In 2014 the Victorian Parliament passed legislation to significantly extend the mandatory requirement for alcohol interlocks. This initiative came into force on 1 October 2014. All drink-drivers in Victoria whose driver licences or learner permits are cancelled must now fit an alcohol interlock to any vehicle they drive once relicensed. Alcohol Interlocks are required for all: Probationary and learner drink-drivers at all BAC levels; First time drink-drivers with a BAC over 0.07; First time drink-drivers with a BAC under 0.07 whose driver licences are cancelled; All repeat drink-drivers; Drivers committing offences such as refusing to provide a breath or blood sample, or culpable driving under the influence of alcohol. The minimum cancellation period is three months and the minimum alcohol interlock condition six months. VicRoads is now managing first-time drink-drivers whose driver licence or learner permit is cancelled and who record a BAC reading of less than 0.10. Courts continue to manage all other drink-drivers. As part of the changes, concrete criteria have been introduced for the removal of alcohol interlock conditions. Both VicRoads and the Courts will use these criteria. A new IT system supports the program. This article outlines the policy decisions behind the new legislation and the challenges in implementing the expanded alcohol interlock program.